2019
DOI: 10.1177/1471082x19825523
|View full text |Cite
|
Sign up to set email alerts
|

A penalized approach to covariate selection through quantile regression coefficient models

Abstract: The coefficients of a quantile regression model are one-to-one functions of the order of the quantile. In standard quantile regression (QR), different quantiles are estimated one at a time. Another possibility is to model the coefficient functions parametrically, an approach that is referred to as quantile regression coefficients modeling (QRCM). Compared with standard QR, the QRCM approach facilitates estimation, inference and interpretation of the results, and generates more efficient estimators. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…2; it is therefore possible, starting from these partial benchmark reference curves, define intermediate benchmarks useful in the short and medium term. Sottile et al (2019) suggested a penalized method that can address the selection of covariates in the QRCM modelling framework "directly on the parameters of the conditional quantile function [and] using information on all quantiles".…”
Section: Frontier Qrcm Modelmentioning
confidence: 99%
“…2; it is therefore possible, starting from these partial benchmark reference curves, define intermediate benchmarks useful in the short and medium term. Sottile et al (2019) suggested a penalized method that can address the selection of covariates in the QRCM modelling framework "directly on the parameters of the conditional quantile function [and] using information on all quantiles".…”
Section: Frontier Qrcm Modelmentioning
confidence: 99%
“…Because the number of components is unknown a-priori, following Pan and Shen (2007); Städler et al (2010) and Sottile et al (2020), to account for shrinkage we select G by employing the modified Bayesian Information Criterion (BIC) (Schwarz et al, 1978): …”
Section: Simulation Studymentioning
confidence: 99%
“…to allow for skewed data and b i ∼ T 2 (0, ) with degrees of freedom.We assumed the following true values for the model parameters: γ = (−1.5, 2.5, 1), β = (2, 0.5, −1) and = 0of components is unknown a-priori, following Pan and Shen (2007); St ädler et al (2010) andSottile et al (2020), to account for shrinkage we select G by employing the modified Bayesian Information Criterion (BIC)(Schwarz et al, 1978): BIC = −2 log(L) + ν f log(N), (4.4)…”
mentioning
confidence: 99%
“…SCAD and MCP type penalties also mitigate the estimation bias of the LASSO. Sherwood and Maidman, 2020 and Sottile et al, 2020 give suites of penalization methods for variable selection in quantile regression.…”
Section: Variable Selection In Quantile Regressionmentioning
confidence: 99%